Disentangling Technological Traditions: Comparative Analysis of Chaînes Opératoires of Painted Pre-Hispanic Ceramics From Nariño, Colombia - Klesner Catherine; Crawford Rosie; Losada Lucero Aristizábal; Arévalo Marcela Bernal; Campos-Quintero Lina María; Arroyo Felipe Cárdenas; Cabrera María Camila Maya; Jaramillo Paula Andrea Murillo; Fernández David Alejandro Pérez; Sáenz-Samper Juanita; Uribe-Villegas María Alicia; Martinón-Torres Marcos (Open Archaeology)
Occurring throughout the Americas, ceramics with negative decoration have been variously used as archaeological markers of chronology, provenance, ethnic affiliation, or cultural interaction. In the highlands of the adjacent regions of Nariño (Colombia) and Carchi (Ecuador), they are recovered and discussed frequently, but the lack of technical studies has prevented any conclusive inferences about their technology, craft organisation, or diachronic evolution. Here we present the first comparative analysis of the chaînes opératoires of three ceramic wares – Capulí, Piartal, and Tuza – based on a large sample from multiple sites. Combining geometric morphometrics, bulk chemistry, microscopy, and microanalysis, we provide high-resolution characterisation of each ware before comparing their chaînes opératoires. We demonstrate that Capulí and Piartal share decorative features and production pathways, which we interpret as indicating the direct knowledge transmission and interaction between their makers. Similarity in vessel morphology and clay sources between Piartal and Tuza ceramics suggests continuity between these two technological traditions, but new decorative techniques and designs in Tuza vessels are strongly indicative of exogenous influences. This study has implications for regional archaeology but also offers a model for the nuanced comparison of ceramic traditions in other areas (for an extended summary in Spanish, see Supplementary Material).